Tracheotomy Outcomes in 64 Ventilated COVID‐19 Patients at a High‐Volume Center in Bronx, NY. (27th January 2021) - Ahmed, Yasmina; Cao, Angela; Thal, Arielle; Shah, Sharan; Kinkhabwala, Corin; Liao, David; Li, Daniel; Parides, Michael; Mehta, Vikas; Ow, Thomas; Smith, Richard; Schiff, Bradley A.
Abstract : Objectives/Hypothesis: The COVID‐19 pandemic has resulted in a dramatic increase in the number of patients requiring prolonged mechanical ventilation. Few studies have reported COVID‐19 specific tracheotomy outcomes, and the optimal timing and patient selection criteria for tracheotomy remains undetermined. We delineate our outcomes for tracheotomies performed on COVID‐19 patients during the peak of the pandemic at a major epicenter in the United States. Methods: This is a retrospective observational cohort study. Mortality, ventilation liberation rate, complication rate, and decannulation rate were analyzed. Results: Sixty‐four patients with COVID‐19 underwent tracheotomy between April 1, 2020 and May 19, 2020 at two tertiary care hospitals in Bronx, New York. The average duration of intubation prior to tracheotomy was 20 days ((interquartile range [IQR] 16.5–26.0). The mortality rate was 33% (n = 21), the ventilation liberation rate was 47% (n = 30), the decannulation rate was 28% (n = 18), and the complication rate was 19% (n = 12). Tracheotomies performed by Otolaryngology were associated with significantly improved survival ( P < .05) with 60% of patients alive at the conclusion of the study compared to 9%, 12%, and 19% of patients undergoing tracheotomy performed by Critical Care, General Surgery, and Pulmonology, respectively. Conclusions: So far, this is the second largest study describing tracheotomy outcomes in COVID‐19 patients in the United States. Our early outcomes demonstrate successful ventilation liberation and decannulation in COVID‐19 patients. Further inquiry is necessary to determine the optimal timing and identification of patient risk factors predictive of improved survival in COVID‐19 patients undergoing tracheotomy. Level of Evidence: 4—retrospective cohort study Laryngoscope, 131:E1797–E1804, 2021